(untitled) (Baltic Journal of Sport and Health Sciences, 2015)
Research background. The hypothesis for this study was that functional ischemic episodes in cardiac muscle during intensive exercising are characteristic of non-athletes and research aim was to find out if individual functional fitness could be revealed by registering ST-segment depression during various type of exercising. Methods. Non-athletes and well-trained runners were involved in the study. Three separate studies (first – increasing intensity of exercising; second – intensive exercise bout; third – continuous aerobic exercising) were performed. Twelve leads EGC were registered; heart rate (HR) and ST-segment depression were taken for analysis. Results. Elite runners exhibited better functional fitness, i.e. were able to perform higher increase in workload, and lower HR values during the same intensity of exercising. The significant differences between cohorts were observed in the dynamics of ST-segment depression. There were no significant changes at onset of incremental exercising in both cohorts, but after reaching some intensity of exercising transient ischemic episodes were registered in the cohort of non-athletes (the first study ). The same type of differences between cohorts was observed at onset of maximal vertical jumping (the second study) and even during the performance of continuous aerobic exercising (the third study). Conclusions. Functional ischemic episodes in cardiac muscle during exercising is characteristic of non-athletes but not of well-trained athletes, and the ST-segment depression could be used as an important index of ECG in the formation of feedback about exercise dosage control during health promotion exercising. Keywords: monitoring, heart rate, ST-segment depression